Pengaruh Penggunaan Metode Lattice terhadap Hasil Belajar Perkalian Kelas IV SD Negeri 19 Palembang - Elvira Indah Sundari; Ilham Arvan Junaidi; Masagus Firdaus (Journal on Education, 2024)
Multiplication is the act of repeatedly adding the same integer results in multiplication. Initial observations at SD Negeri 19 Palembang revealed that pupils had trouble multiplying by more than one digit, which contributed to their poor learning outcomes. The lattice method is a multiplication method that can be used as a solution to students' difficulties in multiplication. This study sought to ascertain whether the lattice approach had any impact on the learning results for multiplication in class IV SD Negeri 19 Palembang. The type of research used in this study was one group pretest-posttest experimental research, which took the form of a pre-experimental design. 25 students from class IV A made up the sample for this study. According to the findings, the average score from the beginning of the exam rose from 67.88 to 76.24 at its conclusion. Additionally, the results of the Paired Sample T-Test used to test the hypothesis show that H0 is not accepted since tcount = 7.7633 > ttable = 2.064. This indicates that the application of the lattice technique has a considerable impact on the learning results for multiplication in class IV SD Negeri 19 Palembang. Therefore, it can be stated that the lattice method's use affects the learning results for multiplication in class IV SD Negeri 19 Palembang.